A conceptual framework for the quality evaluation of sustainability reports. Issue 1 (2014) - ,; ,; ,
<x xml:space="preserve">Abstract</x> Purpose – This paper aims to outline a conceptual framework for the quality evaluation of web‐based sustainability reports (SRs) aiding managers in determining and evaluating quality criteria for the sustainability report of their company. Design/methodology/approach – The paper reviews quality criteria in existing standards and guidelines on sustainability reporting and identifies research gaps. A conceptual framework including a multi‐method approach for the quality evaluation of SRs is developed and evaluated. Findings – Existing standards and guidelines on sustainability reporting mainly focus on the content of the reports and neglect common information systems (IS) acceptance criteria such as ease of use and visual appeal. The proposed framework directly involves different stakeholder groups and research methodologies into the quality evaluation process. Research limitations/implications – The limitations of the research approach offer a number of starting points for future research. The proposed framework needs to be further evaluated by a larger number of test users in a more natural use setting. Practical implications – The application of a multi‐method approach as well as the direct involvement of the stakeholders allows for an in‐depth quality evaluation of SRs, enabling reporting companies to meet the readers' demand for information on economic, environmental and social activities of the reporting company. Common acceptance factors from the field of IS should be integrated into existing standards and guidelines on sustainability reporting. Coaching of the users through help functions, wizards, instructional videos or avatars is desirable. Originality/value – The proposed framework applies innovative technologies such as eye‐tracking and software‐supported attention analysis. By applying the framework to a set of sample reports, its usefulness and applicability are demonstrated. <ack> <x xml:space="preserve">Acknowledgements</x> This work is part of the project "IT‐for‐Green" (Next Generation CEMIS for Environmental, Energy and Resource Management). The "IT‐for‐Green"‐project is funded by the European regional development fund (Grant Number W/A III 80119242). The authors greatly appreciate the support provided by all involved project partners. They would also like to thank the participants of the experimental evaluation, industry workshops and expert interviews as well as the anonymous reviewers and Marita Imhorst who provided useful insights, support and substantive feedback during the research process. </ack>